Circulating miRNAs in localized/locally advanced prostate cancer patients after radical prostatectomy and radiotherapy - Zedan, Ahmed H. (Prostate, 2018)
BACKGROUND: Overtreatment is a well‐known clinical challenge in local prostate cancer (PCa). Although risk assessment models have contributed to a better stratification of patients with local PCa, a tailored management is still in its infancy. Over the last few decades, microRNAs (miRNAs) have shown promising results as biomarkers in PCa. The aim of this study was to investigate circulating miRNAs after management of local PCa. METHODS: The relative expression of four miRNAs (miRNA‐21, ‐93, ‐125b, and miRNA‐221) was assessed in plasma from 149 newly diagnosed patients with local or locally advanced PCa. Real‐time polymerase chain reaction was used for analysis. A baseline sample at time of diagnosis and a follow‐up sample after 6 months were assessed. The patients were grouped in an interventional cohort (radical prostatectomy, curative intent radiotherapy, or androgen‐deprivation therapy alone) and an observational cohort (watchful waiting or active surveillance). RESULTS: In the interventional cohort, levels of both miRNA‐93 and miRNA‐221 were significantly lower in the follow‐up samples compared to baseline z = −2.738, P = 0.006, and z = −4.498, P < 0.001, respectively. The same observation was recorded for miRNA‐125b in the observational cohort (z = −2.656, P = 0.008). Both miRNA‐125b and miRNA‐221 were correlated with risk assessment r = 0.23, P = 0.015, and r = 0.203, P = 0.016 respectively, while miRNA‐93 showed tendency to significant correlation with the prostatectomy Gleason score (r = 0.276, P = 0.0576). CONCLUSIONS: The current results indicate a possible role of miRNA‐93 and miRNA‐221 in disease monitoring in localized and locally advanced PCa. Larger studies are warranted to assess the clinical impact of these biomarkers.